(untitled) (Saúde Ética & Justiça, 2009)
The Internet spread since the 1990s has given substantial changes in the dynamics of social interactions, being responsible for the development of a globalized culture in which traffic of information is processed by new communication paradigms. Therefore the impact of the Internet regarding professional formation has been discussed by several outlines of knowledge — in order to establish guidelines and protocols that can provide the basic frameworks for efficient Online Education projects. This study aimed at providing a feasibility analysis of resorting the Internet as a support tool for presencial courses in the teaching-learning process in Dentistry. 143 morning classes students from the School of Dentistry at University of São Paulo(FOUSP) - 70 of them attending their second semester and 43 attending their eighth semester - took the survey about Internet and Computer knowledge. Results show that the evaluated public got good skills to use the Internet as a pedagogical tool in their professional formation.